Is This Stalking? Perceptions of Stalking Behavior Among Young Male and Female Adults in Hong Kong and Mainland China - Chan, H.; Sheridan, Lorraine (Sage Publications, 2017)
Most studies of stalking are conducted with samples from individualist cultures. Little is known about the phenomenon within collectivist cultures. The present study is arguably the first stalking study conducted in Hong Kong. Specifically, this study investigates a large sample of Asian college students’ (N = 2,496) perceptions of stalking behavior, potential reasons for stalking, and coping strategies that may be employed by stalking victims. Associations between these variables and gender and culture (Hong Kong vs. Mainland China) were also explored. Gender was more strongly associated with perceptions of stalking behavior than was culture. Gender was less strongly associated with perceptions concerning motivations for stalking and the effectiveness of coping strategies that may be employed by stalking victims than was culture. Effect sizes for all associations with culture were small, perhaps due to a high degree of similarity between the two cultures examined. The findings are generally supportive of similar results produced by previous work conducted within individualistic Western cultures, suggesting that stalking and the way that it is perceived may be universal in nature. This study concludes with the argument that legislation against stalking needs to be extended to non-Western countries, such as Hong Kong and Mainland China, as antistalking laws are relatively scarce outside Western industrialized countries.